Teacher at the Center of Attention – Subjective Perception of Difficulty and Satisfaction of Elementary and Kindergarten Teachers - Jonek, Henrieta (Open Access Indonesia Journal of Social Sciences, 2023)
This article is aimed at the teaching profession and describing partial outcomes of subjective perception of workload and satisfaction of educators. The research uses the measurement tools Assessment scale: Perception of the burden of work activities and Life satisfaction questionnaire. The paper is focused on four dimensions – the subjective perception of workload related to the teaching process, related to the extracurricular activities, satisfaction with the job and satisfaction with one's free time. The research sample consisted of 874 Slovak teachers (232 in kindergarten, 411 in elementary school, 219 in leadership position, 12 “other”). The workload is perceived as a slight burden in the teaching process (x̄ = 2.057), but also outside of it (x̄ = 2.040). In general, teachers are satisfied with their jobs (x̄ = 4.787) and impartial towards their personal free time (x̄ = 4.313). In some areas there was a significant difference between kindergarten and elementary educators in perception of difficulty. Elementary educators deem the workload as more distressing. A significant difference was also demonstrated between the perception of satisfaction with free time between kindergarten teachers, primary education teachers and teachers in management positions, with kindergarten teachers being more satisfied. Our findings point to the need to differentiate the actions of teachers at different levels of education, in their job positions, and to provide them with support for their work well-being and satisfaction.